Workability study of sand-bentonite-cement mixtures for construction of two-phase cut-off wall. (22nd August 2022) - Cheng, Hongzhan; Li, Wentao; Chen, Renpeng; Yi, Yaolin
Highlights: Workability of sand-bentonite-cement is studied for two-phase cut-off wall. Cement causes significant increase in flowability and bleeding. Quick cement–water-bentonite reactions are responsible for workability change. Results from one-phase construction are not applicable directly for two-phase. Abstract: The workability of fresh materials is critical for sand-bentonite-cement cut-off wall; however, previous studies are limited to the one-phase construction method, not the two-phase. Hence, this study attempts to fill the gap. First, series of flowability and bleeding tests on sand-bentonite mixtures were conducted (1st phase); subsequently, cement slurry was added to mixtures (2nd phase) to investigate its effect on the workability. The results indicated that, for sand-bentonite mixtures with required workability for 1st phase of construction, the addition of cement caused significant increase in flowability and bleeding, i.e. reducing the workability for 2nd phase, especially for sodium bentonite. The reason was revealed as the short-term interactions (mainly cation exchange) between bentonite and cement hydration products, reducing water retention capacity and swelling potential of bentonite.